Measures to Mitigate Negative Effects of Post Covid-19 Pandemic on Public Primary School Teaching and Learning: A Case of Kalambo District, Rukwa, Tanzania - Masanyiwa, Angelina; Mwamakula, Frank; Mhagama, Michaela (International Journal For Research In Educational Studies, 2023)
This study aimed to assess the effects of the post-COVID-19 pandemic on public primary school teaching and learning, with a focus on Kalambo District. The research was guided by specific objectives, including identifying the social and economic effects of the pandemic on teaching and learning, as well as determining measures to mitigate its negative impact. The study employed Albert Bandura's Social Learning Theory (1969) as its theoretical framework and a mixed research approach with the convergent parallel research design for data collection. The research included 176 respondents, comprising of District Educational Officer, head teachers, teachers, and students. Data was collected through interviews and questionnaires, and instrument validity was ensured. The findings revealed changes in classrooms, teaching methodologies, and the development of fear among pupils and teachers, along with unfortunate deaths of teachers. Challenges included insufficient resources and government budget allocation. Recommendations encompassed reducing class sizes, improving ventilation, water availability and sanitation, constructing additional schools, providing resources for teaching and learning, and offering modern teaching training. The study determined to, improve public primary school infrastructure, limiting class sizes, and enhancing resources were advised to mitigate future COVID-19 impacts.